Struktur Anatomi Organ Vegetatif Kacang Panjang (Vigna sinensis (L.),var. BCA 02) pada Tingkat Salinitas yang Berbeda - Riza Linda, Ulan, Mukarlina (Universitas Tanjungpura, 2016)
Plants require proper environtmental conditions for growth and development. One of the environmental conditions that put pressure on plants that may result in environmental stress is salinity. Plants will undergo morphological and anatomical changes to be able to adapt to saline environments. The long beans (Vigna sinensis (L.), var. BCA 02) which were used in this research are varieties that are sensitive to salinity and cultivated in the area of Rasau Jaya, West Kalimantan. This research aims to find out the anatomical structure of the vegetative organs of long beans (V. sinensis (L.), var. BCA 02) at the NaCl levels of 2,000ppm, 3,000 ppm and 5,000 ppm. The research was carried out from September to November 2015. The preparations of cross section of vegetative organs (roots, stems and leaves) were made using a paraffin method. Research findings showed that the addition of NaCl caused changes in morphological and anatomical structure of the vegetative organs of long beans which included epidermal thickness, cortex, mesophyll and vascular tissue.